Biogeographical conditions, the transition to agriculture and long-run growth - Michael Bleaney; Arcangelo Dimico (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2008)
We use new data on the timing of the transition to agriculture, developed by Putterman and Trainor (2006), to test the theory of Diamond (1997) and Olsson and Hibbs (2005) that an earlier transition is reflected in higher incomes today. Our results confirm the theory, even after controlling for institutional quality and other geographical factors. The date of transition is correlated with prehistoric biogeography (the availability of wild grasses and large domesticable animal species). The factors conducive to high per capita incomes today are good institutions, an early transition to agriculture, access to the sea and a low incidence of fatal malaria. Geographical influences have been at work in all of these proximate determinants of per capita income.
Keywords: O11; 330; agriculture; geography; growth; institutions; Entwicklung; Landwirtschaft; Geographie; Volkseinkommen; Wirtschaftsgeschichte; Welt